Mass Attenuation Coefficient Measurements of Photoelectric Absorption of Gamma-Rays in Copper Using Coincidence Technique - Mahmoud A. Elawi (Tikrit Journal of Pure Science)
The photoelectric absorption mass attenuation coefficients (m.a.c.) of  ɤ- rays in Cu are measured using a two 3"x3" NaI(Tl) detector coincidence spectrometer at 511, 1173 and 1332keV energy gates using Na-22 and Co-60 point sources. The m.a.c. (in cm²/g) measured by coincidence method were lower than those obtained from direct measurement. Coincidence measurements revealed the coefficients 0.0429, 0.0212 and 0.0205 and direct measurements the coefficients 0.0561, 0.0239 and 0.0220 for the studied energies respectively. The μm (co) /μm (dir) ratios were 0.763, 0.8900 and 0.9345at the three energies mentioned respectively. The coincidence coefficients also behave as those of direct spectra as with change in energy.